An investigation of HCV as a predictor of cognitive decline: The Bio‐Hermes protocol. (31st December 2021) - Wolz, Robin; Bork, Jason; Cordell, Cyndy; Hughes, Lynne; Bullock, Roger Alan; Cerroni, Giulio; Dwyer, John; Mohs, Richard
Abstract: Background: A 2018 NIA‐AA Research Framework extended the biological definition of Alzheimer's disease (AD) from biomarkers of amyloid (A) and tau (T) to include measures of neurodegeneration (N) thus enabling more detailed staging and identification of participants potentially closest to clinical decline (N+) ( AlzheimersDement .2018;14(4):535‐562). This framework is only partially implemented in clinical trials as N is rarely considered a selection criterion. Hippocampal volume (HCV) measured from magnetic resonance imaging (MRI) has been proposed as a widely available, robust tool to define N+ ( AlzheimersDement .2014;10(4):421‐429.e3). Method: Participant selection through N+ will be validated in a sub‐study of the Bio‐Hermes trial planned by the Global Alzheimer's Platform Foundation®. The Bio‐Hermes trial will assess biomarkers of Aβ, phospho‐tau, and neurofilament light in approximately 1, 000 participants in three cohorts: cognitively normal, mild cognitive impairment, probable AD. A baseline MRI will be performed in approximately 200 additional participants randomized in a substudy. A pre‐defined HCV cut‐off from the Learning Embeddings for Atlas Propagation (LEAP) algorithm was identified to define N+ status ( NeuroImage .2010;49(2):1316‐1325). The sub‐study will enrol participants willing to forgo treatment studies for 12 months to allow standardized measures of progression. Correlation with clinical measures and clinical decline will be compared in N+ and N‐ populations in the three cohorts to validate the benefit of full ATN staging in trial design. Result: While most publications using the LEAP algorithm for N+ AD patient stratification define N+ cut‐offs based on HCV percentiles in the analysed dataset ( Neurobiology of Aging . 2012;33:2272–2281, Neurology . 2013;80(12):1124‐1132, , Neurology . 2016; 87(12):1235–124, Alzheimers Dement . 2018;14(7):1076, Alzheimers Dement . 2020; 10.1002/alz.037912), one study deployed percentiles from a healthy reference cohort ( Neurobiology of Aging . 2014;35:808‐818). Based on prior work and simulations of the Bio‐Hermes trial cohorts, the N+ cut‐off was set at HCV=5.4cm 3 . Conclusion: The presented study design validates the use of MRI as inclusion criterion in AD clinical trials to fully implement ATN staging. As MRI is a standard tool during screening for AD clinical trials, additional participant characterisation can be achieved at minimal extra cost and burden, significantly improving trial power.